المبادئ السياسية والوظائف الاقتصادية والاجتماعية في وثيقة المدينة دراسة تحليلية - خليف، محمد صالح أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study deals with the political assets and economic and social functions of the state in the light of Wathiqat al-Madina, a document developed by the Prophet (SAW) in the first year of immigration on the eve of his entry to the city of Yathrib. This document was the basis for the organization of social relations between the citizens of the city who are immigrants and supporters and Jews and some residents of Yathrib who did not enter Islam. This document was drawn up after consultation with all of these parties to obtain a general consensus. This study confirms that the first Islamic state was a constitutional one according to a contract that included all its citizens. The study used the analytical, comparative and argumentative approaches. It analyzed and compared the principles of this document, which comprised 52 articles. The thesis is comparised of five main questions. In their entirety, the chapters have answered the central research questions. It dealt with the meanings of the nation in light of the principles of the document and presented the religious and political manifestations of this concept. Additionally, this thesis extracted from these items constituents of the nation and came to the conclusion that this document includes the necessary ingredients for the establishment of any state and that Muhammad (SAW) was governor of the city until his death. The document presented the links to the Arab society before Islam, and it became clear that the Madinah Constitution had formulated these tribal connections, as determined by the Association of Citizenship and Association of Muslim Brotherhood, which is the basis of rights and duties among the citizens of the state. The thesis dealt with the question of ownership in the Madinah Constitution, compared them to the pre-Islamic era in Arab society, and then the ownership in the city's constitution as an expression of the Islamic system of ownership and the two regimes prevalent in the contemporary world, namely the capitalist system and the socialist system. This was subjected to restrictions on ownership imposed by Islam to reflect the social function of ownership. The study examined the functions of the state and its role in the Islamic economy. This was reinforced by the provisions of the document after the introduction of this research by comparing the nature of the state in the capitalist system with the nature of its role in the socialist system and the nature of its role in the Islamic economy. The research exposed the economic functions of the state based on the terms of the document and how the document organized the movement of transactions. The thesis concludes with a number of recommendations.